2002
DOI: 10.1203/00006450-200212000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Adult Rat Heart after Neonatal Dexamethasone Therapy

Abstract: Glucocorticoid treatment in preterm babies to prevent chronic lung disease causes myocardial hypertrophy and increased myocardial protein content. Although these changes are thought to be transient, there is evidence that dexamethasone (DEX) induces permanent myocardial abnormalities as well. We investigated whether a therapeutic course of neonatal DEX in rat pups produces anatomic and biochemical alterations in rat hearts during adult life. Twenty-four rat pups were treated with DEX on d 1, 2, and 3 (0.5, 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
48
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 26 publications
3
48
0
1
Order By: Relevance
“…Previous studies have reported neonatal glucocorticoid effects in rats using various regimens of dexamethasone administration (5,7,20,28,53,54). In the present protocol, dexamethasone was administered over a longer period (P3 through P6) in tapering doses in an attempt to mimic the longer treatment regimen cited by many neonatal intensive care units (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported neonatal glucocorticoid effects in rats using various regimens of dexamethasone administration (5,7,20,28,53,54). In the present protocol, dexamethasone was administered over a longer period (P3 through P6) in tapering doses in an attempt to mimic the longer treatment regimen cited by many neonatal intensive care units (17).…”
Section: Discussionmentioning
confidence: 99%
“…It is not designed to evaluate the effects of a 2-day, four-dose dexamethasone protocol used in many neonatal units for treatment of refractory hypotension but rather to provide a tapering dose of dexamethasone during a postnatal age in the rat that corresponds to the neurodevelopmental time point at which human premature infants have historically received prolonged glucocorticoid therapy for CLD (46 -48). This is in contrast to animal models that use short courses or single doses of dexamethasone (5,7,20,28,53,54).…”
mentioning
confidence: 97%
“…A major motivation for this therapy is the promotion of surfactant production and lung maturation and to induce closure of the ductus arteriosus (6,34,43,45,47). Dexamethasone decreases the duration of ventilatory support and lowers the incidence of chronic lung disease (13,23,33,50).Dexamethasone therapy, however, may lead to unfavorable long-term sequelae, including decreases in neuromotor and cognitive function (4,15,30,36,37,55), and may also lead to left ventricular abnormalities and metabolic dysfunction (5,14,17,24). A report of lipid intolerance in infants treated with dexamethasone highlights this potential for long-term metabolic dysfunction (2).…”
mentioning
confidence: 99%
“…Dexamethasone therapy, however, may lead to unfavorable long-term sequelae, including decreases in neuromotor and cognitive function (4,15,30,36,37,55), and may also lead to left ventricular abnormalities and metabolic dysfunction (5,14,17,24). A report of lipid intolerance in infants treated with dexamethasone highlights this potential for long-term metabolic dysfunction (2).…”
mentioning
confidence: 99%
“…The development of these systems has been studied in the rat (30), but very few data are available for the (preterm) human situation. Thus, although species differences may be of influence, this model is frequently used, and several effects of dexamethasone treatment found in humans, including early transient hypertrophy, were also found in the rat model (11,22,27,34).…”
mentioning
confidence: 99%